The RSV F p27 peptide: current knowledge, important questions - Rezende, Wanderson; Neal, Hadley E.; Dutch, Rebecca E.; Piedra, Pedro A. (Frontiers in Microbiology, 2023)
Respiratory syncytial virus (RSV) remains a leading cause of hospitalizations and death for young children and adults over 65. The worldwide impact of RSV has prioritized the search for an RSV vaccine, with most targeting the critical fusion (F) protein. However, questions remain about the mechanism of RSV entry and RSV F triggering and fusion promotion. This review highlights these questions, specifically those surrounding a cleaved 27 amino acids long peptide within F, p27.